Role of hospital-based cancer registries: A decade of experience of cancer cervix from a Tertiary Care Centre, India - Shalini Rajaram; Sruthi Bhaskaran; Shagun Sinha; Sarla Agarwal (Wolters Kluwer Medknow Publications, 2014)
Background: Hospital-based registries are important tools for policy formulations and region-specific data creation, particularly in case of cervical cancer, which is preventable by an effective screening program. Objective: To study the epidemiological characteristics and trends in cervical neoplasia in an urban population over a decade. Materials and Methods: Data were collected from the histopathological records of patients from January 2000 to December 2009. Results: A total of 1315 gynecological malignancies were reported with cancer cervix being the most common (70.4%) with a progressive increase in the number from 56 in 2000 to 157 in 2009. Squamous cell cancer was the predominant variant with majority in advanced stage. The mean age was 50.1 years with doubling of cases in the ≤35-year category. Of 742 colposcopic biopsies performed, cervical intraepithelial neoplasia (CIN) 1 was diagnosed in 34.9%, CIN 2 in 11.8%, CIN 3 in 7.8%, and microinvasive cancer in 0.8% cases. Conclusion: Though screening programs are in place, their effectiveness can be judged only by such reporting systems that aid in modifying the current cancer control strategies.